WifeLive: Screenlife dengan Dekonstruksi Alur Zigzag - Fajar Indayani; Rustim Rustim (Universitas Negeri Medan, 2023)
WifeLive film™s talks about hyperhonest, the phenomenon of sharing too honestly on social media that is experienced by a pregnant wife. This phenomenon is then packaged in the form of Screenlife, which is a visual storytelling with events displayed on a computer screen, gadget, or smartphone. Narratively, the hyperhonest issue is developed through a zigzag plot deconstruction process that tells the story in an uncoordinated way to build new meanings. This film will show the phenomenon of virtual world propaganda that is used to lies that are often done just for the sake of momentary pleasure.